Sugar-Cane, Trinidad, B.W.I. - No. 47 - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of East Indian labourers standing amidst the sugar cane stalks. Affixed to the back of the postcard are two Trinidad and Tobago 1/2 penny stamps.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry; Sugarcane; Working class; East Indians